Motivating the Students to Study the Basics of Digital Signal Processing by using Virtual Learning Environment - Marozas, V.; Dumbrava, V. (Elektronika ir Elektrotechnika, 2010)
The course “Discrete time signal processing” might seem for students as being quite theoretical and difficult to understand. We have introduced several innovations into the course at the beginning of the year 2008. This paper describes the experience in teaching the basics of discrete signal processing by using MATLAB based projects involving synthesis, processing and analysis of sounds as well as the variety of tools available in virtual learning environment. It is well known that information and knowledge is grasped easier if more senses are activated during the learning process. Thus several lab works were designed with the goal to synthesize the sound of the bell, to design the digital reverberator, to analyze the noise of computer ventilators and others. Modern virtual learning environments (Moodle, WebCT) are usually used mere as depositories of learning materials. In our case, we used almost all the tools available in the virtual learning environment including: assessments, assignments, discussion forums, electronic submission of lab reports, announcements and usage statistics reports as the teacher tool. The anonymous course evaluation results by the students are presented in the final part of the paper.